2009
DOI: 10.1111/j.1524-4733.2009.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do Type 2 Diabetes Mellitus-Related Chronic Complications Impact Direct Medical Cost in Four Major Cities of Urban China?

Abstract: The high economic burden raised by diabetes and its complications challenges the Chinese health-care system. It implicates an urgent need of intervention to prevent the development of long-term complications among the diabetic population, especially on the development of complications in high-cost body system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 18 publications
9
41
1
Order By: Relevance
“…Our study showed that DM cost increased with the number of complications. This result underlines the evidence from other studies showing that complication-induced direct medical cost causes a high economic burden in diabetic patients [22, 27]. The longitudinal data showed a significant growth of percentage of patient with at least one complication.…”
Section: Discussionsupporting
confidence: 84%
“…Our study showed that DM cost increased with the number of complications. This result underlines the evidence from other studies showing that complication-induced direct medical cost causes a high economic burden in diabetic patients [22, 27]. The longitudinal data showed a significant growth of percentage of patient with at least one complication.…”
Section: Discussionsupporting
confidence: 84%
“…Using China, an upper-middle income country, as an example, population-level primary prevention of diabetes- through media campaigns- costs well under one USD per capita per year. However, treatment of uncomplicated diabetes costs nearly 1000USD and treatment of complicated diabetes costs nearly 2,500USD [26,27]. …”
Section: Reviewmentioning
confidence: 99%
“…8 , 9 Several large clinical trials have demonstrated that tight blood glucose control correlates with a reduction in the microvascular complications of diabetes. 10 The American Diabetes Association (ADA) has designated HbA1C level of <7% as a goal of optimal blood glucose control 11 and the American Association of clinical endocrinologists has further recommended HbA1C levels of <6.5%.…”
Section: Introductionmentioning
confidence: 99%